KEMAMPUAN INVESTIGASI MATEMATIS SISWA DALAM MATERI POLA BILANGAN DI SMAN 01 PONTIANAK - Abdi, Egy; Suratman, Dede; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims describe the students mathematical investigative abilities onÂ number patterns material at Senior High School 01 Pontianak. This research uses descriptive qualitative methods. Data collection using tests, interviews, and documentation. The subjects in this study were 35 students of class XI MIPA 7 of Senior High Shool 01 Pontianak. Data analysis shows that students' mathematical investigative ability at the thought process stage specializes in number pattern material classified in the medium category with an average score was 76.63. The ability of students' mathematical investigations at the stage of the thought process of submitting guesses on material number patterns is classified in the medium category with an average score was 74.46. The ability of students' mathematical investigations at the stage of the thought process consider the material on number patterns belonging to the medium category with an average score was 73.18. The ability of students' mathematical investigations at the stage of the process of thinking generalization in the material pattern of numbers is classified in the medium category with an average score was 58.82.Â Keywords: Mathematical Investigative, Number Patterns